(3eG HYO GdEeHQGWhQjIs (3OQGSI dJacjc GdfXGe GdCeQjcjs - (3JhO, EjeGfhjds; (3eUWai, eMeO eSJLjQs ((3GdbGgQIs (3OGQ SWhQs, 2004)
(3jJfHC gPG GdcJGH HSbhW hTjc ddEeHQGWhQjI GdCejQcjI(B. (3hgh aj Pdc jOb fGbhS GdNWQ aj GJLGgjf(B: (3aef LgI jMPQ GdhdGjGJ GdeJMOI ef bQH JMdd gjefJgG hEeHQGWhQjJgG; hjfHg ef LgI CNQi (B"(3ef jYfjge GdCeQ(B" (3Edi GdYed Ydi JSQjY gPG GdSbhW(B. (3aEjeGfhjd JhO GdPj JfHC HGfgjGQ GdEeHQGWhQjI GdShajGJjI bHd hbhYg, jMPQ GdhdGjGJ GdeJMOI ef eUjQ eTGHg, hjHjf gTGTI fXGegG hVYag, hjQi Cf QchOgG GdGbJUGOj GdeVWQO hJQGLY bOQGJgG GdGbJUGOjI hGdYScQjI hGdCjOjhdhLjI, dG jSeMGf dgG HGdSjWQI aYdjkG Ydi YGde CUHM TOjO GdGJSGY, hjfHFGf HGfgjGQ MdegG GdEeHQGWhQi(B. (3Sha JNSQ GdhdGjGJ GdeJMOI eYQcJgG GdCNjQI aj GdgjefI Ydi GdYGde dCfgG abOJ bOQJgG Ydi GdSjWQI Ydi eMGhQ GdYGde GdGbJUGOjI (B((3ChQhHG, QhSjG, GdjGHGf, GdUjf(B)(3, hEPG CUQJ Ydi Cf JKHJ bhJgG GdgGFdI, adf JadM CcKQ ef Cf JcTa ddYGde Yf YLRgG, hJSqQY aj SbhW EeHQGWhQjJgGs
12 20
Keywords: (3GdEQgGHs; (3GdhdGjGJ GdeJMOI GdCeQjcjIs -- (3YdGbGJ NGQLjIs